2012
DOI: 10.7314/apjcp.2012.13.10.5161
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Smad7 in Cholangiocarcinoma: Prognostic Significance and Implications for Tumor Metastasis

Abstract: Background: There are few molecular markers known to predict cholangiocarcinoma (CCA) prognosis. Smad7 has a certain relationship with epithelial-mesenchymal transition (EMT), but its relevance to CCA in unclear. Therefore expression and clinical significance of Smad7 in CCA was the focus of this study. Methods: Expression of Smad7, E-cadherin and vimentin was assessed in 41 patients with CCA by immunohistochemistry and analyzed for associations with clinical parameters. Results: Smad7 and vimentin expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…In addition, the lack of correlation between I-SMAD mRNA and protein levels was recently noticed in pancreatic cancer55. Although multiple IHC analyses of SMAD7 have firmly established the correlation of SMAD7 protein expression with better prognosis of cancer patients565758, the SMAD7 mRNA levels did not show such clinical relevance5960. Collectively, these studies underscore the importance of post-transcriptional regulation of SMAD7 to coordinate TGFβ signalling in developmental and pathological conditions.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the lack of correlation between I-SMAD mRNA and protein levels was recently noticed in pancreatic cancer55. Although multiple IHC analyses of SMAD7 have firmly established the correlation of SMAD7 protein expression with better prognosis of cancer patients565758, the SMAD7 mRNA levels did not show such clinical relevance5960. Collectively, these studies underscore the importance of post-transcriptional regulation of SMAD7 to coordinate TGFβ signalling in developmental and pathological conditions.…”
Section: Discussionmentioning
confidence: 99%
“…This process drives cancer progression and metastasis by promoting angiogenesis and inducing EMT [32]. Smad7 is highly expressed in cholangiocarcinoma and involved in cancer EMT and metastasis and is a potential prognostic cancer marker [20]. Smad7 also inhibits melanoma metastasis to bone [21].…”
Section: Introductionmentioning
confidence: 99%
“…Three CNV-TFs ZSCAN1, RFX1 and NFIC targeted two SMAD proteins SMAD3 and SMAD7. Study of Huang et al showed that SMAD7 was highly expressed in cholangiocarcinoma and might be a potential prognostic indicator for clinical assessment [54]. ZSCAN1 also targeted TGFBR1 which can activate SMAD proteins.…”
Section: Resultsmentioning
confidence: 99%